Effect of casein phosphopeptide-amorphous calcium phosphate on the flexural strength of enamel-dentin complex following extracoronal bleaching - Diatri Nari Ratih; Hendargo Agung Pribadi (Faculty of Dental Medicine, Universitas Airlangga https://fkg.unair.ac.id/en, 2015)
Background: Bleaching can affect the mechanical properties of enamel-dentin complex, such as flexural strength. Casein phosphopeptide-amorphus calcium phosphate (CPP-ACP) is often used following bleaching treatment to reduce hypersensitivity and to increase demineralization of tooth. Purpose: The purpose of the study was to investigate the effect of CPP-ACP on the flexural strength of enamel-dentin complex following extracoronal bleaching. Methods: Forty-eight enamel-dentin plates (size 8 x 2 x 3 mm) were randomly assigned into 6 groups, each consisted of 8 samples. Group 1, no bleaching and immersed in artificial saliva. Group 2, no bleaching, CPP-ACP application only. Group 3, bleaching using 15% carbamide peroxide. Group 4, similar to group 3, except application of CPP-ACP for the times between bleaching. Group 5, bleaching with 40% hydrogen peroxide. Group 6, similar to group 5, except application of CPP-ACP for the times between bleaching. Flexural strength of each enamel-dentin plate was tested by threepoint bending test using universal testing machine. Results: The results showed that 15% carbamide peroxide and 40% hydrogen peroxide significantly reduced flexural strength of enamel-dentin (216.25±26.44 MPa and 206.67±32.07 MPa respectively). Conversely, application of CPP-ACP following both bleachings increased flexural strength (266.75± 28.27MPa and 254.58±36.59 MPa respectively). A two-way Anova revealed that extracoronal bleaching agents significantly reduced flexural strength (p<0.05). Conclusion: Extracoronal bleaching agents reduce flexural strength, whereas application of CPP-ACP following bleaching either with 15% carbamide peroxide or 40% hydrogen peroxide can increase the flexural strength of enamel-dentin complex.